PENGARUH PELAKSANAAN KEBIJAKAN SUNSET POLICY, TAX AMNESTY, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Alfiyah, Nur; Latifah, Sri Wahjuni (Universitas Muhammadiyah Malang)
This research aims to provide empirical evidence of the influence of implementation of SunsetPolicy, Tax Amnesty, and Tax sanctions on individual’ Taxpayer who run the business activitiesand work free in KPP Pratama Dompu. The number of respondents in this research are 58individual taxpayers who run the business activities and work free which was listed in KPPPratama Dompu. The type of data used in this research is primer data obtained from thedistributions of questionnaires containing the answers from respondents. The analysis methodof this research is logistic regression analysis. The result indicates that sunset policy, tax amnesty, and tax sanctions have significant effect on taxpayer compliance of individual in DompuDistrict.Keywords: Sunset Policy, Tax Amnesty, Tax Sanctions, and Taxpayer Compliance.